Gradasi Kualitas sebagai Strategi Penanganan Destinasi Pariwisata di Tepian Sungai Kapuas - Ridho Fajar Abuyahman, Ridho Fajar Abuyahman; Muhammad Subhansyah Ikram, Muhammad Subhansyah Ikram; Putu Ayu Vindytha Amanda Putri, Putu Ayu Vindytha Amanda Putri (Politeknik Negeri Pontianak, 2025)
Abstract: Kapuas River is one of the city's key assets in attracting tourists, especially those located on its side, however, these tourist destinations have not maximized their potential. Tourist destinations located on the banks of the Kapuas River are still not well-organized. One of the causes is that these tourist destinations still stand alone even though they are in inclusive areas. Based of these problems, tourist destinations located on the banks of the Kapuas River require a quality gradation assessment that can identify the characteristics of destinations on the Kapuas River, so that they can produce a handling strategy. This research was conducted in the Kapuas River area of ​​Pontianak City, West Kalimantan. The observed areas were the Alun-Alun Kapuas Park, the Kadriah Palace, and the Khatulistiwa Monument. With the discovery of this gradation, it can be concluded that each area has its quality and can be developed according to the character of each area which supports and is related to each other.